Pemaknaan Pria yang Bertahan dalam Abusive Relationship - Muh Egi Rahmadi; Asniar Khumas; Ahmad Ridfah (Journal on Education, 2023)
Dating is a process between individuals meeting each other with the aim of establishing a relationship as a life partner. This study aims to determine the meaning of men who persist in abusive relationships. Criteria for male participants who have experienced an abusive relationship. The research method used is qualitative with data collection techniques using semi-structured interviews. The research data analysis technique used the interpretative Phenomenological Analysis (IPA) method. The results of data analysis showed that the participants of the same form of violence and the meaning of men who persisted in abusive relationships showed a desire to protect their partners, maintain and maintain the relationships they had lived. desire to make sacrifices, hope to be appreciated by a partner, positive self-acceptance of violence, learning to improve self-ability and relationships. The results of this study can contribute in providing an overview of the meaning of love for men who experience dating violence.